Distribution of races and Tox genes in Pyrenophora tritici-repentis isolates from wheat in Argentina - Moreno, Maria Virginia (2015)
Tan spot, caused by Pyrenophora tritici-repentis, isa common disease in wheat-growing regions of Argentina. Inthis study 65 isolates of P. tritici-repentis obtained from differentcultivars and wheat regions of Argentina were assessedfor their virulence on six wheat cultivars/lines (Glenlea,Salomouni, Katepwa, M-3, 6B365 and 6B662) and for thepresence/absence of the Tox genes based on a PCR approach.Thirty-six isolates were assigned to races, of which races 4and 8 were dominant. Results for molecular analysis of ToxA,ToxB, ToxB-like and toxb genes showed that 57 isolates possessedthe ToxA gene whereas only one isolate possessed ToxAand ToxB genes. There was no correlation between races andthe toxin genotypes. It is suggested that P. tritici-repentis exhibitsa complex race structure in Argentina.